i assume it means expand
(2x - 4)(2x - 4)
= 4x^2 - 8x - 8x + 16
= 4x^2 - 16x + 16
2007-11-10 08:11:34
·
answer #1
·
answered by Jay 4
·
0⤊
0⤋
a. x^2 + 6x + 10 6/2 = 3 3^2 = 9 10 + x = 9 x = -a million subtract a million Ans. (x^2 + 6x + 9) b. x^2 + 2x + 8 2/2 =a million a million^2 = a million 8 + x = a million x = -7 subtract 7 Ans. (x^2 + 2x + a million) c. x^2 - 8x - 6 -8/2 = -4 -4^2 = sixteen -6 + x = sixteen x = 22 upload 22 (x^2 -8x + sixteen) d. 2x^2 - 4x + 10 2(sqrt 2)x = -4 (sqrt 2) x = -2 x = -2/(sqrt 2) (sqrt 2)x -2/(sqrt 2) (-2/(sqrt 2) )^2 = 4/2 = 2 10 + x = 2 x = -8 subtract 8. Ans. (2x^2 - 4x + 2) e. 5x^2 + 26x + 5 2(sqrt 5)x = 26 (sqrt 5)x = 13 x = 13/(sqrt 5) ((sqrt 5) + 13/(sqrt 5))^2 (13/(sqrt 5))^2 = 169/5 = 33.8 5 + x = 33.8 x = 28.8 upload 28.8 (5x^2 + 26x + 33.8) f. 4x^2 + 5x - 8 5/2 = 2.5 (2x + 2.5)^2 2.5^2 = 6.25 -8 + x = 6.25 x = 14.25 upload 14.25 (4x^2 + 5x +6.25) (Sorry, I gave too a lot strategies) -JD-
2016-12-16 04:32:03
·
answer #2
·
answered by walpole 4
·
0⤊
0⤋
Nope. Common mistake.
It's 4x^2 - 16 x + 16
This'll help you understand: (2x-4) ^2 is the same as (2x - 4)(2x-4). Use FOIL and multiply it out
General equation: (a - b)^2 = a^2 - 2ab + b^2
2007-11-10 08:12:32
·
answer #3
·
answered by Someone 4
·
0⤊
0⤋
wait if it is (2x-4)to the power of two then the answer is 4x to the power of 2-16x+16
2007-11-10 08:13:40
·
answer #4
·
answered by wicked 2
·
0⤊
0⤋
Answer is something else, it is:
4x^2 +16 -16x
2007-11-10 08:12:34
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
It's somethign else.. Look
(2x-4)^2
(2x-4)(2x-4)
4x^2-8x-8x+16
4x^2+16
Ohh.. ahaha.. my bad
2007-11-10 08:13:20
·
answer #6
·
answered by Kelly<3 3
·
0⤊
0⤋
no
4x^2-16x+16
when squaring you multiply 2 * -4y as well and double it
2007-11-10 08:12:41
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
i am learning this too lol but the answer i think is think 4x but i'm not sure (i'm not exactly sure how do this )
2007-11-10 08:14:00
·
answer #8
·
answered by Emily~ 4
·
0⤊
0⤋